RELATIONSHIP BETWEEN AGE AND MATERNAL PARITY WITH HYPEREMESIS GRAVIDARUM IN PUJUD HEALTH CENTER, PUJUD DISTRICT, ROKAN HILIR REGENCY, RIAU PROVINCE IN 2023 - khoirun nisa; Eva Ratna Dewi; Suryani (Mitra Husada Health Internasional Conference (MIHHICo), 2023)
The impact of pregnant women experiencing morning sickness and this problem is not immediately handled by health workers, the impact will result in excessive nausea, vomiting (Hyperemesis Gravidarum), dehydration or disturbance of body electrolyte fluids, decreased body weight. Lack of food and oxygen can cause tissue damage which can endanger the health of the mother and the fetus she contains (Hidayati, 2018). The research was carried out using an analytic correlation design with a cross sectional approach. The research was conducted by describing the cases of patients who had hyperemesis gravidarum in the medical records, then looking for the relationship between the variables studied using statistical calculations. (5.4%). while for the parity of the respondents, the majority of parity primiparous pregnant women experienced hyperemesis gravidarum, a total of 11 mothers (7.4%). From the results of the study it can be concluded that there is a relationship between age and parity with the incidence of hyperemesis gravidarum at the Pujud Health Center.